The unhappy divorce of sociology and psychoanalysis diverse perspectives on the psychosocial (Studies in the psychosocial series, 2014)
"Why does the field of sociology in the United States often overlook or marginalize psychoanalytic concepts like anxiety, defence mechanisms, and the unconscious dating back to Sigmund Freud? The Unhappy Divorce of Sociology and Psychoanalysis shows that this was not always the case, and that the field of contemporary sociology can benefit from inclusion of psychoanalytic perspectives. It features twenty-one essays by well-known scholars in and outside the United States - including Nancy Chodorow, George Cavalletto and Catherine Silver, Jeffrey Prager, Neil Smelser and Gilda Zwerman, alongside junior scholars who are all working on how sociology, psychoanalysis, and the psychosocial interrelate. Beginning with a preface by Jeffrey Alexander and a foreword by Craig Calhoun, the articles consider the history of the relationship, ongoing debates, and the need for psychosocial analyses when studying racism, gender, immigration, class and the housing crisis, trauma and social movements (among other applied topics). The book makes a lively case for the significance of tapping into interdisciplinary approaches, including the psychosocial, if sociology is to offer cutting-edge research on a range of contemporary social issues requiring multi-dimensional insights. "--